The marketing director's role in business planning and corporate governance - Michaluk, Gerald (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2007)
Corporate governance is a hot topic, as is the need for marketing to operate at board level. But no-one has yet brought the two issues together. This book changes that. Gerald MichIaluk builds on the latest research to help marketing directors incorporate marketing systems and best practice into a board's decision-making process. Michaluk outlines marketing's key role in alerting the board to market conditions that merit adjustment of the corporate strategy, thus ensuring that strategy is based on sound intelligence and grounded in market reality. The book is illustrated with examples from a h.
The Marketing Director's Role in Business Planning and Corporate Governance; CONTENTS; ACKNOWLEDGEMENTS; ACRONYMS USED IN THE TEXT; CHAPTER 1: BOARD LEVEL IMPLICATIONS; CHAPTER 2: WHO DO WE SERVE AS DIRECTORS?; CHAPTER 3: THE TOOLS AND AIDS AVAILABLE TO THE MARKETING DIRECTOR; CHAPTER 4: MARKETING ADVANTAGE FROM TOP DOWN AND BOTTOM UP; CHAPTER 5: CORPORATE GOVERNANCE AND RISK ASSESSMENT; CHAPTER 6: INNOVATION AND BUSINESS PLANNING RESEARCH; CHAPTER 7: BUSINESS PLANNING PROCESS; CHAPTER 8: BENCHMARKING PERFORMANCE; CHAPTER 9: CORPORATE SYSTEMS TO AID MANAGEMENT AND CONTROL.
Includes bibliographical references (pages 275-276) and index.
Print version record.
John Wiley and Sons
Keywords: Corporate governance; Marketing executives; Gouvernement d'entreprise.; Responsables marketing; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Corporate governance; Marketing executives